1981
DOI: 10.1177/0300985881018s0609
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Mesangioproliferative Glomerulonephritis in Pigtailed Macaques (Macaca nemestrina)

Abstract: Mesangioproliferative glomerulonephritis was found in 28 of 113 pigtailed macaques (Macaca nemestrina) that died in 1977. In five it was considered severe enough to cause significant renal dysfunction; in two of these it was the cause of death. The basic lesion was a proliferation of mesangial cells and deposition of mesangial matrix in the mesangial stalk, resulting in various degrees of stalk expansion and increased lobulation of the glomerular tuft. Preliminary immunofluorescence and ultrastructural studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 3 publications
(5 reference statements)
0
14
0
Order By: Relevance
“…Giddens and colleagues (1981) reported that 14% of adult nemestrine macaques dying from spontaneous disease had GN and concurrent IgM glomerular deposits. However, very limited IgM deposits thought to contribute to the pathogenesis of the severe forms of the disease in nemestrine macaques (Boyce, Giddens, and Seifert 1981) similar to the more widespread drug-ADA complexes in some of the case study monkeys (Tables 3-4). Often, the antigen is unknown in the IC-related granular deposits in spontaneous glomerular disease in monkeys.…”
Section: Ihc Findings In Monkey Glomerular Diseasementioning
confidence: 78%
See 3 more Smart Citations
“…Giddens and colleagues (1981) reported that 14% of adult nemestrine macaques dying from spontaneous disease had GN and concurrent IgM glomerular deposits. However, very limited IgM deposits thought to contribute to the pathogenesis of the severe forms of the disease in nemestrine macaques (Boyce, Giddens, and Seifert 1981) similar to the more widespread drug-ADA complexes in some of the case study monkeys (Tables 3-4). Often, the antigen is unknown in the IC-related granular deposits in spontaneous glomerular disease in monkeys.…”
Section: Ihc Findings In Monkey Glomerular Diseasementioning
confidence: 78%
“…However, very limited IgM deposits were found in clinically normal nemestrine macaques without renal disease consistent with Brack’s marmoset studies, similar to the very limited IgM deposits observed in control monkeys from case 5 (Table 1). Antigen - IgM ICs in mesangium are thought to contribute to the pathogenesis of the severe forms of the disease in nemestrine macaques (Boyce, Giddens, and Seifert 1981) similar to the more widespread drug - ADA complexes in some of the case study monkeys (Tables 3–4).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…19 Interstitial lesions include periglomerular lymphocytic infiltrates, focal to diffuse infiltrates of lymphocytes and plasma cells in the interstitium, and linear to diffuse fibrosis of the renal parenchyma. [4][5][6][7]12 However, macaques experimentally infected with simian immunodeficiency virus (SIV) appear to have a higher incidence of MesPGN or focal segmental glo- merulosclerosis (or both). 1,11 To our knowledge, this is the first report of CGN and MesPGN associated with IgA deposition in a macaque.…”
Section: Nonhuman Primatesmentioning
confidence: 99%